Relationship between Oil Prices and Stock Prices in BRICS-T Countries: Symmetric and Asymmetric Causality Analysis - Abubakirova, Aktolkin; Syzdykova, Aziza; Dosmakhanbet, Assan; Kudabayeva, Lyazzat; Abdulina, Gulnar (International Journal of Energy Economics and Policy, 2021)
In this study, by considering the period between January 2010 and December 2019 of BRICS-T countries, the relationship between oil prices and stock prices was examined through the Hatemi-J asymmetric causality test (2012). The stationarity levels of the series were determined by Augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) unit root tests. Hatemi-J (2012) asymmetric causality test, which takes into account the presence of asymmetric information in financial markets by distinguishing positive and negative shocks, was used. Accordingly, hidden relationships that could not be detected using the symmetric causality test were revealed with the help of the asymmetric causality test. Keywords: BRICS-T, oil prices, stock prices, asymmetric causality JEL Classifications: C23, G15, Q40. DOI: https://doi.org/10.32479/ijeep.10487